Agriculture Challenges: Decline of Farmers and Farmland (Study from Indonesian Family Life Survey) - Anandita, Della Ayu; Patria, Kinanti Zukhrufijannah (EP FEB UNS, 2016)
The challenge of agricultural sector in Indonesia nowadays is about land ownership which affected farmer’s welfare. Farmers in aggregates are decreasing year by year, followed by decreasing farm land because of the land reform. Another story of farmer’s income affected the land ownership of the farmers. Most of them choose to sell their own land to the land lords because of the lower income. And the lack of regeneration because farmers children choose to have a job outside agriculture sector. This paper is research about the real condition of Farmers in Indonesia between three factor of land ownerships, land reform, and lack of regeneration. Our investigation to secondary data show our hypothetical judgment: there is declining amount of farmers in Indonesia in community level. Meanwhile, that phenomenon support by evidence that there is declining farmland in community level. This study can be considering for policy implication in agriculture reform in Indonesia.Keyword : land ownership, land reform, lack of farmer regeneration, farmer’s welfare